Macroinvertebrate population dynamics, community composition and diversity patterns of two coastal lakes in northern KwaZulu-Natal, South Africa - Campbell, Kaylee Maria (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The 2018 South African National Biodiversity Assessment (NBA) identified eight freshwater lakes of national ecological importance and a lack of understanding of their biology. The assessment further called for baseline foundational data for their conservation. Aquatic invertebrates are considered to be reliable and sensitive biological indicators of environmental and water quality changes, and understanding aquatic invertebrate dynamics in these systems will provide a comprehensive understanding of how they can be better protected. The NBA also highlighted a gap in data associated with ecological response to landscape developments and climate change (mainly below average precipitation and increased temperatures) and how this contributes to aquatic resource conservation. This further complicates the modelling of important ecological thresholds and hampers the prediction of possible responses of these ecosystems to environmental changes. This gap informed the aims and rationale of this dissertation; to identify longer-term spatiotemporal trends in aquatic invertebrate communities in Lake Sibaya and Lake Mzingazi and to determine whether the surrounding land use changes could lead to long-term changes in aquatic invertebrate communities of both lakes by comparing recent survey data with historical datasets. In Chapter 2, this dissertation investigated the population dynamics of freshwater shrimp, Caridina africana in Lake Sibaya and Mzingazi and compared the data to that of 1975 study published by Hart (1981). This was done to assess any changes in the C. africana populations due to the considerable changes in land use and weather patterns that have occurred in the last 48 years in and around the systems. Results from Lake Sibaya and Lake Mzingazi were also compared to determine any differences in urban and agricultural stressors presented to C. africana populations. This chapter hypothesised that increases in anthropogenic pollution, invasive species and other habitat modifications at Lake Sibaya and Lake Mzingazi would lead to (1) reductions in shrimp densities and changes in population dynamics when comparing with the 1975 data from Hart (1981). Additionally, it was predicted that (2) Caridina africana abundances found at Lake Mzingazi would be lower than those found at Lake Sibaya (3) due to different water quality variables associated with land use. Results showed that C. africana population densities at Lake Sibaya and lake level recordings had experienced significant decreases since 1975 with densities being significantly lower in 2021. Additional differences seen in 2021 when compared to 1975 were that females were more abundant than males, individuals between the sizes of 3mm and 5mm were most abundant instead of those in the smallest size class (<0.83mm "“ 1.67mm) and females only dominated size classes above 4mm instead of all size classes above 2.5mm. Populations at Lake Sibaya were negatively correlated with nitrate concentrations in 2021 and populations at Lake Mzingazi were negatively correlated with temperature according to generalised linear models. These results emphasized the importance of pollution mitigation, sustainable water abstraction and the maintenance of natural water temperature ranges in the conservation of lentic C. africana populations. There was also no evidence that urbanisation and agriculture presented different threats to freshwater shrimp populations. In Chapter 3, this dissertation aimed to quantify the littoral aquatic invertebrate diversity and assemblage patterns from Lake Sibaya and Lake Mzingazi to provide comprehensive baseline datasets for these coastal systems. This chapter also aimed to investigate the impacts of landscape developments and habitat change on aquatic invertebrate communities by understanding significant water quality parameters as drivers of community variation. Predictions for Chapter 3 were that increases in agricultural and anthropogenic disturbance and habitat modification will lead to (1) aquatic invertebrate community composition at lakes Sibaya and Mzingazi being structured according to water quality variables that stem from surrounding land-use activities, leading to (2) differing community structures at each lake. Lastly, it was hypothesised that (3) the presence of the invasive snail Tarebia granifera would likely be affecting the aquatic invertebrate diversity and composition of both lakes. According to linear models, aquatic invertebrate abundance at Lake Sibaya was negatively affected by salinity, lake level and phosphate concentration, and positively associated with temperature. Taxa richness and Pielou's evenness at the lake were negatively associated with conductivity and nitrate concentrations respectively. The aquatic invertebrate community at Lake Sibaya also followed typical seasonal patterns. At Lake Mzingazi, Pielou's evenness was negatively associated with nitrate and ammonium concentrations and no typical seasonal patterns were evident in the community composition. Communities at Lake Mzingazi also exhibited resilience despite changes in physicochemical parameters, emphasising the difficulty in predicting aquatic community response to habitat modification due to lake-specific community resilience. Tarebia granifera populations at Lake Sibaya were found to negatively affect invertebrate diversity scores according to generalised linear models. Additionally, no individuals of Melanoides tuberculata were found in either system indicating the possibility that these native snails may have been outcompeted by their invasive counterpart. The prevalence of significant stressors associated with habitat disturbance and the unexpected results seen at Lake Mzingazi emphasized the importance of monitoring aquatic invertebrate communities in response to climate change and associated land use developments to adequately understand the long-term threats these changes pose to freshwater ecosystems and biodiversity conservation.
Keywords: Indicators (Biology); Lakes -- South Africa KwaZulu-Natal; Sibayi, Lake (South Africa); Lake Mzingazi Dam; Biological monitoring -- South Africa KwaZulu-Natal; Biodiversity; Geospatial data -- South Africa KwaZulu-Natal; Land use Planning -- South Africa KwaZulu-Natal